PROSES KERJASAMA INTERNASIONAL ANTARA PEMERINTAH PROVINSI JAWA TIMUR DENGAN PEMERINTAH PERANCIS UTARA DALAM MENERAPKAN KONSEP “BLUE ECONOMY” DI KAWASAN MADURA KABUPATEN SAPEKE - Haryanto, Ichwan (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis study describes the process of East Java Provincial Government and the Provincial Government of northern France to carry out international cooperation in the region in their efforts to apply the concept of Blue Economy that becomes a common goal. The background in this activity is the economic sector in East Java under consideration to conduct cooperation with the planned application of the concept of the Blue Economy. While the concept of Blue Economy itself is a form of economic activity in order to maximize the results of marine resources to be a supporter of economic sectors in the region that have the potential of marine wealth that can be managed optimally. From this background, the question that arises is how the East Java Provincial Government and the Provincial Government of Northern France have international cooperation in an effort to implement the concept of the Blue Economy. The question was studied by using the theory of international cooperation, Paradiplomacy, and the Blue Economy. In its activities the East Java Provincial Government and the Provincial Government of Northern France have international cooperation by making several stages called little diplomacy.Keywords : Blue Economy, Paradiplomacy, International CooperationDOI:https://doi.org/10.33005/jgp.v3i01.1958